Constructing the poetic text At Al-Kumait bin Zaid Al-Asadi (Journal of the College of Basic Education, 2022)
Poetry reached its zenith just before the sunrise of Islam, so its language was a prelude to the revelation of the Holy Qur’an, and thus God Almighty challenged the Arabs in their language to come up with the same style and miraculousness, even with one verse. Islamic poetry has enjoyed a great status among critics, narrators, and scholars, and our poet (Al-Kumait bin Zaid Al-Asadi) is one of the great poets of the Islamic era, who had a great impact in providing this era with a number of new styles and traditions in his poetry, which called on narrators and critics to celebrate his poetry and pay attention to it as a phenomenon of poetic phenomena of that era.